Evolution of third-trimester pregnancy terminations in France. (May 2020) - Cordier, Anne-Gael; Thubert, Thibault; Dussaux, Chloé; Santulli, Pietro; Dommergues, Marc; Picone, Olivier; Benachi, Alexandra
Abstract: Objective: To study changes in the reasons for third-trimester termination of pregnancy (TOP) for fetal anomalies over a 20-year period in France. Study design: We compared a consecutive series of third-trimester TOPs from a single centre in 2005–2014 to those performed by Dommergues et al. in a similar centre in 1986–1994, using the same criteria. Main outcome measures: The process leading to late TOP, using the same categories in both studies. Results: In the present series, 205 of 1409 TOPs were performed in the third trimester, vs. 305/956 in the historical series. There were 33 (16.1 %) diagnoses missed at the screening before the third trimester, 55 (26.8 %) cases in which the anomaly was impossible to diagnose until the third trimester, 86 (42 %) cases in which fetal prognosis could not be established until the third trimester despite earlier diagnosis, 31 (15.1 %) TOPs postponed to allow more time for the women/couples to contemplate, versus respectively 113 (37 %), 55 (18 %), 122 (40 %), and 15 (5%) in the historical series. Conclusion: There was a significant drop in the rate of anomalies missed earlier. The increase in late TOP due to couples requiring additional time for contemplation might result from changes in counselling processes.